Human resource management strategies to improve organizational performance in the digital era - Sari, Sindi Fatikah; Rahdeana, Pina; Nurdiana, Editya (Jurnal Mantik, 2025)
The advancement of digital technology has transformed human resource (HR) management, including in Small and Medium Enterprises (SMEs) in Majalengka Regency. This study investigates the impact of digital HR strategies on organizational performance using a quantitative survey of 50 SMEs. Results show a strong positive correlation (r = 0.78; p < 0.05) between digital adoption and performance, with an average 25% efficiency increase. Despite benefits in recruitment, training, and evaluation, key challenges include employee skill gaps (54%) and budget constraints (48%). The study recommends digital training, infrastructure support, and incentives to help SMEs enhance competitiveness and productivity in the digital era. To address the research foundation more explicitly, this study is guided by the following problem formulation: How do digital technology-based human resource management strategies influence organizational performance among SMEs in Majalengka Regency? Accordingly, the research seeks to answer three key questions: (1) What is the extent of digital technology adoption in HR functions within SMEs? (2) What challenges are commonly encountered in implementing digital HR practices? (3) How significantly does the adoption of digital HR strategies contribute to improvements in organizational performance? These questions form the analytical basis of the study and ensure a focused investigation aligned with the research objectives